Design and Implementation of Active Antennas for IoT-Based Healthcare Monitoring System - MUSA, UMAR; MOHD SHAH, SHAHARIL; A. MAJID, HUDA; MAHADI, ISMAIL AHMAD; A. RAHIM, MOHAMAD KAMAL; YAHYA, MUHAMMAD SANI; ZAINAL ABIDIN, ZUHAIRIAH (Ieee Acces, 2024)
T This work presents the design and implementation of active antennas as a part of a healthcare monitoring system that is based on the Internet of Things (IoT). The monitoring system comprises a SEN11547 pulse sensor and an LM35 temperature sensor for measuring heart rate in Beats Per Minute (BPM) and body temperature in Degree Celsius (◦C). This data is then sent to the ThingSpeak IoT platform, which necessitates the integration with the NodeMCU ESP-32S Wi-Fi module to ensure the availability of data. Two dual-band (2.4 GHz and 5.8 GHz) microstrip patch antennas, one with a PIN diode and one without, are fabricated using Rogers Duroid RO3003™ substrate. Both antennas have dimensions of 41 × 44 mm2 . In order to achieve a dual-band operation at 2.4 GHz, a slot in the shape of an inverted letter U is introduced, to the existing patch which generates a 5.8 GHz frequency band. By controlling the PIN diode’s ON and OFF state, the active antenna can switch between a single band of 5.8 GHz and a dual-band of 2.4 GHz and 5.8 GHz. At both frequencies, the measured radiation patterns exhibit bidirectional and directional characteristics in the E-plane, whereas an omnidirectional pattern can be observed in the H-plane. In terms of nonlinear characteristics of the antenna, the third-order intermodulation distortion products (IMD3) frequencies are generated within an input power range of 0 to 20 dBm from the two-tone nonlinear measurements. Specifically, the IMD3 at 2.4 GHz is measured at −36.18 dBm and −47.19 dBm at 5.8 GHz. Additionally, the measurement showed that the 1-dB gain compression point (P1−dB) was not detected at 2.4 GHz, indicating linear behavior within the RF input power range. However, at 5.8 GHz, the P1−dB was observed at an RF input power level of 13.8 dBm, suggesting linear functionality up to this power level. The experimental data are obtained from ten participants with ages ranging between 18 and 40 years old for 10-minutes duration with a 1-minute step size which implies 10 samples. For comparison and validation, the measurements are compared with the commercially available Laird Connectivity 2.4GHz/5.8GHz dipole antenna. It can be observed that the heart rate ranges from 85 BPM to 92 BPM for the active antenna whereas for the reference antenna, the values range from 84 to 90 BPM, which implies a good agreement. On the other hand, the body temperature ranges from 29 to 37◦C for the active antenna and from 30 to 36◦C for the reference antenna, which infers a good agreement as well. Therefore, it is shown that the proposed dual-band active antennas in this work can be effectively integrated into the IoT-based healthcare monitoring system.